Retraction: Plasma-grafted amidoxime/metal–organic framework composites for the selective sequestration of U(vi). Issue 5 (23rd April 2020) - Li, Fengbo; Li, Xiaoyu; Cui, Pu; Sun, Yubing
Abstract : Abstract : Retraction of 'Plasma-grafted amidoxime/metal–organic framework composites for the selective sequestration of U(vi )' by Fengbo Li et al., Environ. Sci.: Nano, 2018, 5, 2000–2008.